The computation of elementary unitary matrices. - Lehoucq, R. B. (ACM transactions on mathematical software.)
The construction of elementary unitary matrices that transform a complex vector to a multiple of e1, the first column of the identity matrix, is studied. We present four variants and their software implementation, including a discussion onthe LAPACK subroutine CLARFG. Comparisons are also given.